2000
DOI: 10.1046/j.1469-0705.2000.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ultrasound diagnosis of congenital cystic adenomatoid malformation of the lung: a report of 26 cases and review of the literature

Abstract: Conservative management appears to be an adequate medical practice in cases of isolated congenital unilateral cystic adenomatoid malformation of the lung, in the absence of hydrops and/or acute polyhydramnios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…The literature review identified 486 non‐hydropic fetuses with CAM diagnosed prenatally in pregnancies which the parents chose to continue (Table 4)1–4, 6–8, 39, 56, 71–84. Of the total of 645 fetuses (including our 159 cases), there were 18 (2.8%) intrauterine or neonatal deaths and 627 (97.2%) survived.…”
Section: Resultsmentioning
confidence: 99%
“…The literature review identified 486 non‐hydropic fetuses with CAM diagnosed prenatally in pregnancies which the parents chose to continue (Table 4)1–4, 6–8, 39, 56, 71–84. Of the total of 645 fetuses (including our 159 cases), there were 18 (2.8%) intrauterine or neonatal deaths and 627 (97.2%) survived.…”
Section: Resultsmentioning
confidence: 99%
“…14 CCAM is characterized by an excessive overgrowth of the terminal respiratory bronchioles and lung structures with suppression of alveolar growth. 9,15 It seems that decreased apoptosis also plays a role in the pathogenesis. 16 The cause for this malformation is unknown.…”
Section: Discussionmentioning
confidence: 97%
“…A clinically significant pericardial effusion is not a common occurrence after a CCAM resection. [6][7][8][9][10][11][12][13][14][15][16][17] There was no history of central venous catheter insertion. The final pathology report on the pericardial tissue revealed hemorrhagic fibrofatty tissue with no signs of active inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital cystic adenomatoid malformation is a rare entity characterized by the overgrowth of terminal respiratory bronchioles. 6,7 This abnormal lung tissue consists of cysts of variable sizes that communicate with major bronchi through malformed air passages that lack cartilaginous support. These passages tend to collapse during expiration resulting in air trapping and overdistension of cystic structures.…”
mentioning
confidence: 99%